ASSOCIATION OF THIRD TRIMESTER MATERNAL HEMOGLOBIN WITH MEASUREMENT OF NEWBORN’S ANTRHROPOMETRY - Rahman, Farhan Aulia; Anantyo, Dimas Tri; Dewantiningrum, Julian; Haryana, Bambang (Faculty of Medicine, Diponegoro University, Semarang, Indonesia, 2020)
Background: More than 20 million babies are born each year with a body weight of less than 2500 g, and 17% of all births in developing countries. Birth weight plays a role in mortality and morbidity, development and, future health of children. Low birth weight is a significant risk factor for infant death and other physical disorders. Anemia that occurs in maternal can increase the risk of mortality, perinatal morbidity and can affect the state of newborns. Anemia in maternal is related to low gestational age, low birth weight, and increased risk of small infants for gestational age. Research on the relationship of maternal’s hemoglobin levels in third trimester to anthropometric measurement of newborns has never been carried out at Rumah Sakit Nasional Diponegoro (RSND). Objective: This study aims to determine relationship between maternal’s hemoglobin levels in third trimester with anthropometry of newborns. Method: This research was a study with cross sectional design. Data is collected from medical records at RSND. Babies born viewed medical records to determine inclusion criteria in the study. Anthropometric data were collected for newborns and the third trimester hemoglobin level was recorded in pregnant women. Assosiation analytic was performed with chi square test. Results: There was a significant relationship between maternal’s hemoglobin levels in third trimester with measurements of newborn weight, body length, and head circumference. Conclusion: Maternal’s hemoglobin in third trimester affect the measurement of weight, body length, and head circumference neonates.Keywords: anemia, hemoglobin, anthropometry, maternal, newborn